The Evolution of Veiling in "MENA" - MERZOUG, Kheira (My University, 2018)
At the beginning of the modern veil, the meaning was complex, conflictual and evolutionary. This research is a sociolinguistic study that examines the roots of the veil after the historical foundation of the counting of civilizations by the veil, claiming that the beginning of the mantle dates back to a time prior to Islam and Christianity. Not at all like suspicions, it has been more common outside the Middle East community throughout history (Grace 14). As a debatable topic, it has typical implications relevant to some other issues, such as resistance, abuse, character, colonialism and patriarchy, instead of being a just protest. This article examines the concept of the Islamic point of view of human rights and flexibility of expression, as specified in the verses of the Qur'an. The thesis has exposed a short. An introduction to the evolution of the veil in 'MENA' then describes the status of veiled women inside and outside Islamic and non-Islamic Islamic societies. perspectives the diachronic change of the veil over time. In order to reveal a real point of view on the veil in the Algerian society.
Keywords: Linguistic; Religion; Veil; Status of women in Islam